Kontribusi Produksi dan Redaksi Dalam Operasional PT. Jawa Pos Media Televisi - Nazla Taslia Farah; Ety Dwi Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the contribution of production and editorial in the operations of PT. Jawa Pos Media Television (JPMT). As one of the large media companies in Indonesia, JPMT relies on synergy between the production and editorial teams to produce quality content that can meet the public's information needs. The method used in this research is a qualitative approach with in-depth interviews with a number of production and editorial staff, as well as analysis of relevant internal documents. The research results show that the production team plays an important role in providing visual, audio and other technical materials, while the editorial team is responsible for preparing the script, selecting news and maintaining the quality of the information conveyed. These two teams complement each other in order to ensure smooth operations and the achievement of journalistic standards set by the company. This research concludes that effective collaboration between production and editorial is a key factor in JPMT's operational success in the television media industry.